Drivers of interannual and intra‐annual variability of dissolved organic carbon concentration in the River Thames between 1884 and 2013. Issue 6 (15th February 2019) - Noacco, Valentina; Duffy, Christopher J.; Wagener, Thorsten; Worrall, Fred; Fasiolo, Matteo; Howden, Nicholas J.K.
Abstract: The world's longest record of river water quality (River Thames—130 years) provides a unique opportunity to understand fluvial dissolved organic carbon (DOC) concentrations dynamics. Understanding riverine DOC variability through long‐term studies is crucial to capture patterns and drivers influencing sources of DOC at scales relevant for decision making. The Thames basin (United Kingdom) has undergone massive land‐use change, as well as increased urbanisation and population during the period considered. We aimed to investigate the drivers of intra‐annual to interannual DOC variability, assess the variability due to natural and anthropogenic factors, and understand the causes for the increased DOC variability over the period. Two approaches were used to achieve these aims. The first method was singular spectrum analysis, which was used to reconstruct the major oscillatory modes of DOC, hydroclimatic variables, and atmospheric circulation patterns and to visualise the interaction between these variables. The second approach used was generalised additive modelling, which was used to investigate other non‐natural drivers of DOC variability. Our study shows that DOC variability increased by 80% over the data period, with the greatest increase occurring from the beginning of World War II onwards. The primary driver of the increase in DOC variability was the increase in the average value of fluvial DOC over the period of record, which was itself linked to the increase in basin population and diffuse DOC sources to the river due to land‐use and land‐management changes. Seasonal DOC variability was linked to streamflow and temperature. Our study allows to identify drivers of fluvial intra‐annual and interannual DOC variability and therefore empowers actions to reduce high DOC concentrations.